Comparative study on cartilage tissue collected from less- and severely-affected region of osteoarthritic knee - Nurzazlin BZN,; Shamsul BS,; Yahya NHM,; Ruszymah BHI,; Abdul Rani R,; Shiplu Roy Chowdhury, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Culture expanded chondrocytes isolated from non-load bearing region of osteoarthritic (OA) joint has been used to construct tissue engineered cartilage for treatment purposes. The aim of the study was to compare the histological properties of the cartilage tissue and morphological properties of the chondrocytes isolated from less and severely affected OA knee. Human articular cartilage was obtained as redundant tissue from consented patients with late-stage OA undergoing total knee replacement surgery at Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Articular cartilage was graded according to Dougados and Osteoarthritis Research Society International (OARSI) classification. Articular cartilage was classified into less affected (LA; Grade 0-1) and severely affected (SA; Grade 2-3). Cartilage tissue from less and severely affected region was stained with Safranin O staining. Isolated chondrocytes from each group were cultured until passage 4 (P4). Their growth patterns, cell areas, and circularity were compared. LA-cartilage tissue shows uniform spread of safranin O staining indicating intact extracellular matrix (ECM) component. However, SA-cartilage shows significant reduction and unstable staining due to its degraded ECM. LA-chondrocytes showed an aggregated growth compared to SA-chondrocyte that remains monolayer. Moreover, LA-chondrocytes have significantly higher cell area with wider spreading at passage 0 and 4 compared to SA-chondrocytes. It was also found that chondrocyte circularity increased with passage, and circularity of LAchondrocytes was significantly higher than that of the SA-chondrocytes at passage 3. This study demonstrated the considerable difference in the cellular properties for less and severely affected chondrocytes and implication of these differences in cell-based therapy needed to be explored.